Design of a mobile 3D imaging system based on 2D LIDAR and calibration with levenberg–marquardt optimization algorithm - Miao, Ruikai; Liu, Xinyue; Pang, Yajun; Lang, Liying (Frontiers in Physics, 2022)
LIDAR is an excellent means to obtain the information of buildings, forests, bridges, tunnels and many other big scenes, but the high price of 3D LIDAR currently limits its further application. To meet this challenge a mobile 3D imaging system based on 2D LIDAR is proposed. The system has the characteristics of large imaging range and low cost. The composition and implementation principle of each module of the system are introduced in detail and a calibration method for the 3-axis assembly error is proposed. In this method Levenberg-Marquardt (LM) optimization algorithm is used to obtain the optimal value of the 2D LIDAR 3-axis attitude angle, which is used to compensate for the point cloud distortion caused by the assembly error. The experimental results show that the proposed method can effectively reduce the assembly error caused point cloud distortion. This system can meet the application demand of big scenes 3D imaging.